Chitosan-modified fluorescent dye for simple, fast, and in-situ measurement of fungal cell growth in the presence of insoluble compounds. Issue 1 (8th December 2022) - Yang, Zihuayuan; Hu, Xin; Zhang, Funing; Durrani, Samran; Zhang, Jie; Pang, Ai-Ping; Gao, Yichen; Wu, Fu-Gen; Lin, Fengming
Abstract: The measurement of fungal cell growth in submerged culture systems containing insoluble compounds is essential yet difficult due to the interferences from the insoluble compounds like biopolymers. Here, we developed a fluorescent strategy based on chitosan-modified fluorescein isothiocyanate (GC-FITC) to monitor the cell growth of lignocellulosic fungi cultivated on biopolymers. GC-FITC could stain only lignocellulosic fungi ( Tricoderma reesei, Penicillium oxalicum, Aspergillus nidulans, and Neurospora crassa ), but not biopolymers (cellulose, xylan, pectin, or lignin), excluding the interferences from these insoluble biopolymer. Moreover, a linear relationship was observed between the fluorescence intensity of GC-FITC absorbed by lignocellulosic fungi and the biomass of lignocellulosic fungi. Therefore, GC-FITC was leveraged to monitor the cell growth of lignocellulosic fungi when using biopolymers like cellulose as the carbon sources, which is faster, more convenient, time-saving, and cost-effective than the existing methods using protein/DNA content measurement. GC-FITC offers a powerful tool to detect fungal growth in culture systems with insoluble materials. Abstract : A method of measurement of fungal cell growth by dyeing.